Comparative study of efficacy and safety of berberine hydrochloride versus metformin in newly diagnosed prediabetic patients: a randomized clinical trial - Chaudhary, Prashant S.; Deshmukh, Shweta V.; Jaybhaye, Deepali; Kaur, Sukhmeen (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Prediabetes is a growing public health concern in India, with high rates of progression to type 2 diabetes and associated complications. Metformin is widely recommended but has gastrointestinal side effects that may limit adherence. Berberine hydrochloride, a plant-derived alkaloid with antidiabetic properties, has shown promise as an alternative therapy. A randomized, open-label, parallel-group clinical trial was conducted in newly diagnosed prediabetic adults. Methods: Ninety participants were randomly allocated to receive Berberine HCl 500 mg twice daily or Metformin 500 mg twice daily for 12 weeks. Primary outcomes included change in fasting plasma glucose (FPG), postprandial plasma glucose (PPG), and HbA1c. Secondary outcomes included adverse events. Results: Berberine HCl reduced mean FPG from 109.8±4.6 mg/dl to 97.2±3.6 mg/dl (−12.6±2.4 mg/dl) and PPG from 156.4±6.8 mg/dl to 134.6±5.4 mg/dl (−21.8±3.9 mg/dl). Metformin reduced FPG from 110.2±4.8 mg/dl to 99.4±3.8 mg/dl (−10.8±2.5 mg/dl) and PPG from 157.1±7.0 mg/dl to 137.8±5.6 mg/dl (−19.3±4.0 mg/dl). HbA1c decreased by 0.31% in the Berberine group and 0.28% in the Metformin group, with a significant between-group difference at week 12 (p=0.04). Gastrointestinal upset occurred in 20% of Berberine recipients compared to 30% in the Metformin group. Conclusions: Berberine HCl demonstrated glycemic efficacy comparable to Metformin in prediabetic patients, with fewer gastrointestinal adverse events, suggesting its potential as an alternative therapy for individual’s intolerant to Metformin.